2020
DOI: 10.1371/journal.pone.0231651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NUDT15 gene variants in Amazonian Amerindians and admixed individuals from northern Brazil

Abstract: Introduction The nudix hydrolase 15 (NUDT15) gene acts in the metabolism of thiopurine, by catabolizing its active metabolite thioguanosine triphosphate into its inactivated form, thioguanosine monophosphate. The frequency of alternative NUDT15 alleles, in particular those that cause a drastic loss of gene function, varies widely among geographically distinct populations. In the general population of northern Brazilian, high toxicity rates (65%) have been recorded in patients treated with the standard protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…There is a lack of evidence in the literature about current information concerning breast cancer in the population of the Americas, probably due to an underreporting of cases in local communities [ 8 , 14 ]. Furthermore, the traditional populations of Latin America constitute a complex study group due to their human history of miscegenation, which confers them with high levels of interpopulation genetic diversity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a lack of evidence in the literature about current information concerning breast cancer in the population of the Americas, probably due to an underreporting of cases in local communities [ 8 , 14 ]. Furthermore, the traditional populations of Latin America constitute a complex study group due to their human history of miscegenation, which confers them with high levels of interpopulation genetic diversity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample of the American population of the 1000 Genomes Project includes several countries of Latin America, such as Mexico, Peru, Colombia, and Puerto Rico [ 11 ]. Although there is a degree of genetic similarity between AMR and IND populations, the genomic profiles of these countries indicate considerable heterogeneity in terms of Amerindian ancestry contribution, resulting from the different historical aspects of their formation and their degree of genetic admixture, which may explain the differences found in the BRCA1 and BRCA2 gene variants [ 10 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have concluded that the differential mortality rates in Hispanics with ALL are related to a genetic predisposition linked to the Native American ancestry of these populations [ 10 , 11 , 12 , 13 , 14 ]. In fact, many of the genetic variants associated with the toxicity and relapses in the treatment of ALL have been found more frequently in Native American populations or in populations with a high degree of miscegenation involving this ethnic group [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%